Job satisfaction of construction professionals in Kelantan / Nurul ‘Aqilah Othman and Norakmarwati Ishak - Othman, Nurul ‘Aqilah; Ishak, Norakmarwati (2018)
Job satisfaction is the positive emotional state of an employee stemming from experiences with a job. Job satisfaction trends can affect labour market behaviour and influence work productivity, work effort, employee absenteeism and staff turnover. Construction industry is a challenging and demanding environment. In order to successfully complete a construction projects, construction professionals must acquire disposition and capacity, as well as appropriate working conditions. The objectives of the research are to identify factors that influence job satisfaction of construction professionals, their level of job satisfaction and the methods to increase job satisfaction. Questionnaire surveys were conducted among architects, quantity surveyors and engineers in Kelantan. The findings show that current salary as the most important factor that influenced job satisfaction among the construction professionals. On the other hand it is found that they are unsatisfied with salary increment and by giving given bonuses this will increase their job satisfaction.